THEORETICAL ASPECTS OF THE FORMATION OF ACCOUNTING AND CONTROL INFORMATION ON CALCULATIONS WITH PERSONNEL - A. Volkova; T. Rogulenko (Вестник университета)
The article contains an analysis of the essence of accounting and control information, its importance in the system of settlements with personnel, as well as the feasibility of creating an integrated system of accounting and analytical support for personnel management.